The evolution of settlement under the Wallachian Law in the Polish Carpathians. - Kłapyta, Piotr (Balcanica Posnaniensia. Acta et studia, 2024)
The article aims to present the temporal and spatial evolution of settlements on the basis of the Wallachian law in Polish sections of the Carpathian Mountains. A series of thematic maps have been prepared that show the distribution of settlements over a period of more than 300 years, from the second half of the 14th century to the second half of the 17th century. A total of 479 settlements based on Wallachian law or with a certified Wallachian presence have been documented in the physical-geographical area of the Polish Carpathians. They accounted for 28% of all settlements in the region. It should be noted that 70% (339) of these settlements disappeared as a result of the forced population relocations of 1946-1950. Two phases can be distinguished in the history of Wallachian settlement in the Polish Carpathians. The first (from the second half of the 14th century to the end of the 15th century) was mainly related to the military, guardian function of the settlements - 87 new sites were established at that time. The second phase (from the 16th to the end of the 17th century) was rather determined by economic factors, stimulated by climatic changes during the so-called Little Ice Age. During this period, there was an increase in the dynamics of Wallachian settlement, which resulted in the creation of 392 settlements in the mountainous zone, which had poor conditions for farming (above 500 meters above sea level). Settlement under Wallachian law lost its originally ethnic character, becoming a tool for effective colonization of the Carpathians based on pastoral or pastoral-agricultural economy.